Enhancing Teachers’ Competencies through Professional Development Program: Challenges and Benefactions - Apriliyanti, Dewi Listia (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2020)
Teachers’ professional development program is considered to play an important role in enhancing teacher competencies. An observational case study is conducted to observe teachers’ learning process and teachers’ outcomes after learning on the program. Five English teachers who have participated in the professional development program in Indonesia and passed the teachers’ competence test on the program have become key informants of this research. The objectives of the research are to investigate the learning process on the program and challenges faced by the teachers in implementing their teaching knowledge and outcome of teachers after participating in the program. The research has found three essential findings. First, the research found that pedagogic competences and professional competences have become the basic formulation for learning materials that are taught in the program. Second, the research found four obstacles and challenges to implement teachers’ knowledge from the program in their classroom, for instance, innovative teaching methods and creative lesson design. The third, the investigation also discovered the challenges and the benefactions in the implementation of professional learning development as one of the solutions in enhancing English teachers’ competences in Indonesia.